An Analysis of Language Style in Little Buddha Movie - Swantara, Made; Suastini, Ni Wayan; Santika , I Dewa Ayu Devi Maharani (Journal of Language and Applied Linguistics, 2024)
This study focused on the use of language style in the movie "Little Buddha" which shows how language style is used in society. There are two problems to be solved in the study, the types of language styles used on a conversation in the "Little Buddha" movie, and the factor influencing the choice of language style in the "Little Buddha" movie. This study's theoretical framework is based on Joos (1967) states there are five types of language style, namely frozen style, formal style, consultative style, casual style, intimate style, and Holmes (1992) There are four factors in choosing language variation that is participant, setting, topic, and function. The results of this study that there are 25 data of the type of language styles and elaborate factors influencing the choice of language style which is occurred in "Little Buddha" movie and intimate style becomes the most dominant type.